Blockchain in supply chain digital transformation - Clohessy, Trevor (Boca Raton : CRC Press, Taylor & Francis Group, 2023)
Blockchain and distributed ledger technology (DLT) have been identified as emerging technologies that can enhance global supply chain management processes. Given the embryonic nature of the technology, use cases pertaining to how it can be adopted and deployed in supply chain contexts are scarce. This book shares blockchain supply chain use cases across a range of industries including smart cities, food imports, product traceability, decentralised finance, procurement, energy management, consensus mechanism security, and industry 4.0. Given its scope, it is primarily intended for academics, students, researchers, and practitioners who want to learn more about how blockchain can digitally transform global supply chains.
1. A Smart Cities Blockchain Research Agenda--A Bibliometric and Network Analysis Literature Review From 2016 to September 2021Trevor Clohessy2. Breaking Bitcoin at any Cost: Irrational Attacks on Proof-of-Work BlockchainAshish Rajendra Sai3. A Blockchain-Based RegTech System for Product Safety Enforcement: A Case Study of Food Import in ChinaChristophe Viguerie and Robert M. Davison4. Transforming Trade Finance via Blockchain: The We.Trade PlatformDavid Petersen5. Investiging the Role of Permissioned Blockchains as Inter-Organizational Systems for Enabling Supply Chain Digital TransformationLeo Yeung6. Blockchain, Supply Chain and Adoption: A Bibliometric AnalysisColin Callinan et al.7. Blockchain for Product Traceability in the Supply Chain Gary Lee8. Benefits and Barriers to Blockchain Adoption in Industry 4.0 and the Circular EconomyGarry Lohan9. Assimilation of the Blockchain: Exploring the Impact of Blockchain Technology on Supply Chain ManagementTrevor Clohessy10. Blockchain-Based Energy Efficient Supply Chain Management Bavly Hanna et al.
OCLC-licensed vendor bibliographic record.
Keywords: Business logistics -- Data processing; Blockchains (Databases) -- Industrial applications